Chemical supercapacitors: a review focusing on metallic compounds and conducting polymers. Issue 4 (21st December 2020) - Naskar, Pappu; Maiti, Apurba; Chakraborty, Priyanka; Kundu, Debojyoti; Biswas, Biplab; Banerjee, Anjan
Abstract : Material-bank for chemical supercapacitors. Abstract : Capacitors began their journey in 1745, and to date have advanced in the form of supercapacitors. Supercapacitors are one of the advanced forms of capacitors with higher energy density, bridging capacitors and batteries. The energy storage through the formation of an electrical double layer is pivotal for supercapacitor technology. Accordingly, to further improve the energy density, surface faradaic (pseudocapacitive) processes are employed, and henceforth, the journey of chemical supercapacitors commenced. Herein, the materials, mechanisms and fabrication of chemical supercapacitors based on metallic compounds and conducting polymers are discussed in detail. The inherent limitations of these materials are addressed, and the feasible mitigation measures are identified. Poor conductivity, slow diffusion kinetics and rapid structural disintegration over cycling are the common constraints of metallic compounds, which can be overcome by preparing conductive nanocomposites. Thus, versatile conductive nanocomposites of metal oxides, hydroxides, carbides, nitrides, phosphides, phosphates, phosphites, and chalcogenides are elaborated. A lack of structural integrity is the prime obstacle for the realization of conducting polymer-based supercapacitors, which may be solved by forming composites with robust support from carbonaceous materials or metallic compounds. Consequently, the composites of polyaniline, polypyrrole, polythiophene and polythiophene-derivatives are discussed. The historical accounts of early stages of works are emphasised in order to review the developmental pathways of chemical supercapacitors. The construction of full cells and their performance data are presented herein, which synchronize the behaviour of practical scaled-up devices. To the best of our knowledge, this review is the first holistic description of chemical supercapacitors based on metallic compounds and conducting polymers from the first reports to recent advancements.